Antibiotics that target the 50S ribosome subunit: resistance and other considerations - Sutcliffe, Joyce (Henry Stewart Talks, 2008)
Why target the 50S ribosomal subunit?, Analysis of antibacterial market, Mechanisms of drug resistance, Sequestration, How do antibiotics gain entry into cells, Porins, Lack of uptake, Self-promoted uptake drug modification, Target modifications, Drug efflux, Major superfamilies of transport proteins